A place in the world : finding the meaning of home - Mayes, Frances (Crown, 2022)
"A lyrical and evocative collection of personal stories from the #1 New York Times bestselling author of Under the Tuscan Sun, in which the queen of wanderlust reflects on the comforts of home. While Frances Mayes is known for her travels, she has always sought a sense of home wherever she goes. In this poetic testament to the power of place in our lives, Mayes reflects on "home," from the earliest imprint of four walls to the startling discoveries of feeling the strange ease of homes abroad, friends' homes, and even momentary homes that spark desires for other lives. Her musings are all the more poignant after so many have spent their long pandemic months at home. From her travels across Italy-Tuscany, of course, but also Venice and Capri-to the American South, France, and Mexico, Mayes examines the connective tissue among them through the homes she's inhabited. A Place in the World explores Mayes's passion and obsessions with houses and the things that inhabit them-old books, rich food, beloved friends, transportive art. The indelible marks each refuge has left on her and how each home influenced the next serve as the foundations of each chapter. Written in Mayes's signature intimate style, A Place in the World captures the adventure of moving on while seeking comfort in the cornerstone closest to all of us-home"--